Exploring the Interplay of Beauty: Shelley's and Dickinson's Poems through Mead's Theoretical Framework - Jesudas, Roseline (CV. Tripe Konsultan, 2024)
This study uses a symbolic interaction approach, specifically based on George Herbert Mead's ideas, to examine how Percy Bysshe Shelley's